HRM in healthcare: the role of work engagement. Issue 2 (7th March 2016) - Shantz, Amanda; Alfes, Kerstin; Arevshatian, Lilith
Abstract : Purpose: – Due to increasing cost pressures, and the necessity to ensure high quality patient care while maintaining a safe environment for patients and staff, interest in the capacity for HRM practices to make a difference has piqued the attention of healthcare professionals. The purpose of this papers is to present and test a model whereby engagement mediates the relationship between four HRM practices and quality of care and safety in two different occupational groups in healthcare, namely, nurses and administrative support workers. Design/methodology/approach: – Structural equation modeling was used to analyze questionnaire data collected by the National Health Service in the UK as part of their 2011 Staff Survey ( n =69, 018). The authors tested the hypotheses for nurses and administrative support workers separately. Findings: – Training, participation in decision making, opportunities for development, and communication were positively related to quality of care and safety via work engagement. The strength of the relationships was conditional on whether an employee was a nurse or administrative support worker. Originality/value: – This is the first paper to examine the mediating role of engagement on the relationship between four relevant HRM practices in the healthcare context, and outcomes important to healthcare practitioners. The authors also add value to the HRM literature by being among the first to use the job demands resources model to explain the impact of HRM practices on performance outcomes. Moreover, the authors provide insight into how HRM practices affect outcomes in the world's largest publicly funded healthcare service.